Train passenger car floor panel testing using digital image correlation and strain gauges and comparison with finite element modelling. (November 2016) - Braga, Daniel F.O.; Ramos, Tiago; Eslami, Shayan; Tavares, Paulo J.; Infante, V.; de Castro, Paulo M.S.T.; Moreira, P.M.G.P.
Abstract: Weight reduction of passenger railway cars is a recurrent concern, driven by increasing efficiency objectives. The work presented here is part of a project aiming at developing a new solution for a train passenger car floor panel. A design was proposed and an experimental programme sets forth to evaluate its feasibility. Small coupon testing was performed to assess the selected joining processes. A structural detail was also studied for static and fatigue loading in order to evaluate failure modes and locations. A prototype of the structure was built and tested in 3-point bending using electrical strain gauges and digital image correlation. A numerical model of the prototype was built in order to estimate loads during testing and for benchmarking purposes. Highlights: Design for a railway car underframe was proposed. Testing of coupons, detail component and prototype was done. DIC, strain gauges and FEM were compared in prototype testing. CO2 LBW showed poor weld quality and resulted in high distortions. DIC showed to be a valuable tool for structural analysis.